2020
DOI: 10.1186/s10086-020-01906-y
|View full text |Cite
|
Sign up to set email alerts
|

Color change and termite resistance of fast-growing tropical woods treated with kesambi (Schleichera oleosa) smoke

Abstract: Smoke treatment can be used to enhance wood resistance to subterranean termite attack. In this study, kesambi (Schleichera oleosa) wood was pyrolyzed to produce charcoal. The smoke produced as a by-product of pyrolysis was used to treat sengon (Falcataria moluccana), jabon (Anthocephalus cadamba), mangium (Acacia mangium), and pine (Pinus merkusii) wood samples for 1, 2, or 3 weeks. Following the smoke treatment, the wood specimens were exposed to subterranean termites (Coptotermes curvignathus Holmgren) accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…These findings revealed that smoke treatment for samples resulted in different colors (ΔE more than 12) compared with unsmoked samples. In a previous work, similar results for mangium and sengon smoked woods were determined [12,22], Ishiguri et al [25] also determined that wood samples Based on the results displayed in Table 5, unsmoked and smoked samples were significantly different from each other in terms of their L* and b* values. Smoke treatment resulted in samples with a darker color, as indicated by an L* value of smoked wood that decreased to become half of the value of the unsmoked wood.…”
Section: Discoloration Of the Samplessupporting
confidence: 68%
See 3 more Smart Citations
“…These findings revealed that smoke treatment for samples resulted in different colors (ΔE more than 12) compared with unsmoked samples. In a previous work, similar results for mangium and sengon smoked woods were determined [12,22], Ishiguri et al [25] also determined that wood samples Based on the results displayed in Table 5, unsmoked and smoked samples were significantly different from each other in terms of their L* and b* values. Smoke treatment resulted in samples with a darker color, as indicated by an L* value of smoked wood that decreased to become half of the value of the unsmoked wood.…”
Section: Discoloration Of the Samplessupporting
confidence: 68%
“…These findings revealed that smoke treatment for samples resulted in different colors (∆E more than 12) compared with unsmoked samples. In a previous work, similar results for mangium and sengon smoked woods were determined [12,22], Ishiguri et al [25] also determined that wood samples treated with smoke for 200 h showed significant discoloration having deeper color those of exposed of smoke for 100 h.…”
Section: Discoloration Of the Samplessupporting
confidence: 66%
See 2 more Smart Citations
“…Penelitian Bian et al (2015) menyatakan kondisi asap dalam proses pengasapan dipenga ruhi oleh bahan baku, panas dan pengaturan nyala api. Suhu yang baik digunakan dalam proses pengasapan adalah 80 o C -90 o C. Hadi et al (2020b) meneliti pengaruh lama pengasapan pada empat jenis kayu yaitu kayu sengon (Falcataria moluccana), kayu mangium (Acacia mangium), kayu pinus (Pinus merkusii) dan kayu jabon (Anthocephalus cadamba) terhadap perubahan warna kayu dan menguji keawetan kayu dari serangan rayap tanah Coptotermes curvignathus Holmgren. Lama pengasapan yang digunakan meliputi 1 minggu, 2 minggu dan 3 minggu.…”
Section: Prosedur Pengawetan Kayuunclassified